Selected immunohistochemical prognostic factors in endometrial cancer - Markova, Ivana; Duskova, Milada; Lubusky, Marek; Kudela, Milan; Zapletalová, Jana; Procházka, Martin; Pilka, Radovan (International journal of gynecological cancer, 2010)
OBJECTIVE: The objectives of this study were to assess the immunohistochemical expression of p53, bcl-2, c-erbB-2, Ki-67, estrogen (ER) and progesterone (PR) receptors, matrix metalloproteinase-7 and -26 (MMP-7 and MMP-26) in endometrial cancer patients and to assess the relation between steroid receptor positivity and other markers. DESIGN: Experimental prospective study. SETTING: Department of Obstetrics and Gynecology, Department of Genetics, Department of Pathology, Palacký University Medical School and University Hospital Olomouc. METHODS: We studied 144 cases of primary untreated endometrial carcinoma in which the p53, bcl-2, c-erbB-2, Ki-67, ER, PR, MMP-7, and MMP-26 antigens were investigated with the use of immunohistochemical methods. We evaluated the correlations among immunohistochemical staining and the age, International Federation of Gynecology and Obstetrics stage, grading, depth of invasion, and metastatic spread to lymph nodes. RESULTS: Mean age was 65.7 years (range, 34-90 years). p53, bcl-2, c-erbB-2, Ki-67, ER, and PR were positive in 35 (24.3%), 100 (69.4%), 41 (28.4%), 65 (45.1%), 115 (79.8%), and 127 (88.1%) cases, respectively. Matrix metalloproteinases were evaluated in a group of 70 patients, wherein MMP-7 was positive in 33 patients (47.1%) and MMP-26 was positive in 40 patients (57.1%). The expression of MMP-7 decreased with higher patient age. p53 and Ki-67 overexpression was found to be related to poor differentiation. Immunostaining for bcl-2 correlated with the positivity of steroid receptors status, whereas immunostaining for c-erbB-2 correlated inversely with ER-positive group of cases. CONCLUSIONS: The overexpression of p53 and Ki-67 seems to indicate a more malignant phenotype, whereas bcl-2 expression in dependence of steroid receptor positivity could contribute to the identification of high-risk tumors.
Keywords: nádory endometria; matrixová metaloproteinasa 7; Carcinoma, Papillary; dospělí; antigen Ki-67; Receptors, Estrogen; Tumor Suppressor Protein p53; Female; Adult; invazivní růst nádoru; ženské pohlaví; Matrix Metalloproteinases, Secreted; lidé; Proto-Oncogene Proteins c-bcl-2; protoonkogenní proteiny c-bcl-2; serózní cystadenokarcinom; Receptors, Progesterone; receptory progesteronu; receptory pro estrogeny; Aged, 80 and over; prognóza; Receptor, ErbB-2; imunoenzymatické techniky; papilární karcinom; receptor erbB-2; Matrix Metalloproteinase 7; prospektivní studie; nádorové biomarkery; Aged; Prospective Studies; metaloproteinasy secernované do matrix; nádorový supresorový protein p53; Immunoenzyme Techniques; Prognosis; Ki-67 Antigen; Biomarkers, Tumor; lidé středního věku; Endometrial Neoplasms; senioři nad 80 let; senioři; Neoplasm Invasiveness; Cystadenocarcinoma, Serous; Middle Aged; Humans